Mothers with Intellectual Disabilities Raising Children with Intellectual Disabilities - Parchomiuk, Monika (Journal of Intellectual Disability - Diagnosis and Treatment, 2017)
The article describes the results of research involving mothers with intellectual disabilities. The aim of author's own study was to learn about maternal experiences related to raising children with intellectual disabilities. The experiences were described in greater detail in relation to the diagnosed disabilities of their children, early stage of their upbringing, problems emerging during their development, involvement of significant (supporting) persons. In addition, issues addressed in the study included description of maternal competences, the subjective meaning and essence of motherhood, and perception of the role of one's own disability in acting as a mother. Moreover, factors related to life situation of mothers, their previous experiences, especially experiences in their families of origin and personality features significant for the quality of motherhood, were identified.